Impact of Acquisition of Sumitomo Mitsui Banking Corporation on PT. Bank BTPN, Tbk - Wananda Muhammad Rifki; Aulia Mahdi (Telaah Bisnis, 2023)
This study aims to examine and analyze the financial performance of PT Bank BTPN Tbk., before and after the acquisition by Sumitomo Mitsui Banking Corporation in 2014. Acquisition is a process in which a company buys majority shares or all shares of another company to expand the business or take over the business. Research is conducted using financial report data for 2010 – 2013 (pre-acquisition) and 2014 – 2018 (post-acquisition). The hypothesis was tested using a significance number <0.05 using parametric statistical tests for normally distributed data and non-parametric statistics for non-normally distributed data. The results showed that the average financial ratios studied (ROA, ROE, NIM, LDR, NPL, CAR, and BOPO) tended to decrease after an acquisition was made. Based on statistical tests, there is a significant difference for ROE, NIM, and LDR and the other ratios (ROA, NPL, CAR, and BOPO) show the opposite.